Secreted frizzled-related protein 3 regulates activity-dependent adult hippocampal neurogenesis - Jang, Mi-Hyeon (2013)
Adult neurogenesis, a process of generating mature neurons from adult neural stem cells, proceeds concurrently with ongoing neuronal circuit activity and is modulated by various physiological and pathological stimuli. The niche mechanism underlying activity-dependent regulation of sequential steps of adult neurogenesis remains largely unknown. Here we report that neuronal activity decreases the expression of secreted frizzled-related protein 3 (sFRP3), a naturally secreted Wnt inhibitor highly expressed by adult dentate gyrus granule neurons. Sfrp3 deletion activates quiescent radial neural stem cells and promotes newborn neuron maturation, dendritic growth and spine formation in the adult mouse hippocampus. Furthermore, sfrp3 reduction is essential for activity-induced adult neural progenitor proliferation and acceleration of new neuron development. Our study identifies sFRP3 as an inhibitory niche factor from local mature dentate granule neurons that regulates multiple phases of adult hippocampal neurogenesis and suggests a novel activity-dependent mechanism governing adult neurogenesis via acute release of tonic inhibition.